The immunogenetics of Graves' disease - Gough, S (1999)
Graves' disease clusters in families, and higher concordance rates in monozygotic compared with dizygotic twins support a genetic basis to the disease. It seems likely that not only are a collection of small genetic effects contributing to this multifactorial complex disease but that susceptibility alleles are common in the general population and are not rare mutations. A combination of population-based case control and family-based studies is required to elucidate the genetic basis to Graves' disease. The author reviews the size and nature of the genetic contribution to disease, the methods used for the detection of susceptibility loci, and the results currently available.